Synthesis of some new 4,5-substituted-4H-1,2,4-triazole-3-thiol derivatives - Cansiz, A; Koparir, M; Demirdag, A (Mdpi, 2004)
In this study appropriate hydrazide compounds, furan-2-carboxylic acid hydrazide (1) and phenylacetic acid hydrazide (2) were converted into 1,4-substituted thiosemicarbazides 4a-e and 5a-e and 4-amino-5-(furan-2-yl or benzyl)-4H-1,2,4-triazole-3-thiols 7 and 10. The 1,4-substituted thiosemicarbazides were then converted into 5-(furan-2-yl or benzyl)-4-(aryl)-4H-1,2,4-triazole-3-thiols 8a-e and 9a-e. In addition, the azomethines 11a-d and 12a-d were prepared from the corresponding arylaldehydes and the 4-amino-5-(furan-2-yl or benzyl)-4H-1,2,4-triazole-3-thiols 7 and 10. The structures of all the synthesized compounds were confirmed by elemental analyses, IR, H-1-NMR and C-13-NMR spectra.
Keywords: 4H-1,2,4-triazole-3-thiols; azomethines; thiosemicarbazides